‘Aqidah al-Tauh id ‘Inda Ibn Taimiyah - Amal Fathullah Zarkasyi (TSAQAFAH, 2011)
There were various explications of the concept of tawhid presented by Muslim scholars in the past, especially among mutakallimun and falasifah, but most of them emphasized on the unity of essence, attribute activities. Ibn Taymiyyah is one of the most celebrated Muslim theologians and regarded by some as mujaddid or reformer on Islamic theological thought. His reformative thought could be discerned from his concept oftawhid, which is deemed unique and worthy of further studies. However, it is not only of his concept that he was regarded as reformer, but also his framework of theological studies. The method employed in this research is literary studies, yet it is also supported by historical, descriptive, inductive and critical analytical method. The finding of this research is that Ibn Taimiyyah’s concept of tawhidconsists of unity of God, unity of Allah worship and the unity of essence and attribute. The first means the belief existence of God as the Creator; the second is the manifestation of belief in the form worship by heart, speech and good deed; the last one is belief in the perfect attributes of Allah based on the Qur’an and Sunnah. He also emphasized that one who does not believe in these three kinds of tawhid, or believe only in the unity of God could not save from the Hell. Regarding the framework, Ibn Taymiyyah restricts that the theological discourses should commit to the Qur’an and Hadits, rely on rational capacity of man, rebuff kalam interpretation and prever revelation from reason.